A Mathematical Model of Cloud Computing in the Economic Fractional Dynamic System - Ibrahim, Rabha Waell; Gani, Abdullah (Springer International Publishing, 2018)
Computing is experiencing much change from client/server to the cloud. The interest for cloud infrastructures is not only introducing in the business domain, but likewise encompasses to government activities. In this work, we suggest a new dynamic system, equilibrium of cloud computing based on fractional calculus. In our preparation, each agent (i.e., each company or government agency) determines between going to appliance the customary on-site computing pattern and acting to the cloud computing model. In this model, separately agent will optimize an entire cost that involves of two mechanisms: the cost of implementing the cloud computing pattern and the effort cost of moving to the cloud computing pattern. We shall impose various types of two-dimensional fractional systems. The method of finding the solution is subjected to bifurcation and bifurcation boundaries to perform a good result in the cloud computing. This method is generalized to the fractional calculus. Therefore, the outcome lets us to training the dynamic evolution of the density of cloud computing.